GEOINFORMATION SYSTEMS OF FORMATION AND USE OF LANDS OF THE NATURAL FUND OF REGIONS: MODERN EDUCATIONAL DIRECTIONS OF PRO-GRAMS OF PREPARATION OF MASTERS: Array - Chang, Liu; Mamonov, K.; Frolov, V.; Kondratyuk, I. (Municipal economy of cities. Series: «Economy science», 2020)
The relevance of the research topic on the development and implementation of master’s programs geographic information systems of formation and use of lands of the natural fund of the regions is proved. The purpose of the study is to determine the directions and features of the development of the educational master's program geographic information systems of formation and use of lands of the natural fund of the regions. In accordance with the set goal the following tasks are solved: substantiation of components of the master's program on geoformation systems of formation and use of lands of natural fund of regions; characteristics of practical aspects of application of the master's program on geographic information systems of formation and use of lands of the natural fund of regions. The components of the master's program on geoformation systems of formation and use of lands of the natural fund of regions are determined. The objectives of the study within the framework of the master's program in geoformation systems of formation and use of lands of the natural fund of the regions are substantiated. The practical aspects of its implementation are determined. The modules of the master's program of formation and use of natural fund lands are offered: directions and features of application of geoformation systems in the field of formation and use of natural fund lands; methods and models used in geoformation analysis; directions and features of formation and use of natural fund lands; implementation of the system of formation and use of natural resources with the use of geographic information systems; development of scientifically sound recommendations for improving the efficiency of formation and use of natural resources. It is established that the development and implementation of a master's program in geographic information systems for the formation and use of natural resources allows the use of modern information systems to solve complex problems of land use, taking into account spatial, environmental and investment factors. On the basis of this program is the training of masters who implement the acquired knowledge in scientific and practical fields, which allows to create conditions for the development of areas of formation and use of natural resources.